Risk Factors of Microbial Keratitis in Uganda: A Case Control Study. (3rd March 2020) - Arunga, Simon; Kintoki, Guyguy M.; Gichuhi, Stephen; Onyango, John; Ayebazibwe, Bosco; Newton, Rob; Leck, Astrid; Macleod, David; Hu, Victor H.; Burton, Matthew J.
ABSTRACT: Purpose : Microbial keratitis (MK), is a frequent cause of sight loss worldwide, particularly in low and middle-income countries. This study aimed to investigate the risk factors of MK in Uganda. Methods : Using a nested case control, we recruited healthy community controls for patients presenting with MK at the two main eye units in Southern Uganda between December 2016 and March 2018. Controls were individually matched for age, gender and village of the cases on a 1:1 ratio. We collected information on demographics, occupation, HIV and Diabetes Mellitus status. In STATA version 14.1, multivariable conditional logistic regression was used to generate odds ratios for risk factors of MK and a likelihood ratio test used to assess statistical significance of associations. Results : Two hundred and fifteen case-control pairs were enrolled. The HIV positive patients among the cases was 9% versus 1% among the controls, p = .0003. Diabetes 7% among the cases versus 1.4% among the controls, p = .012. Eye trauma was 29% versus 0% among the cases and controls. In the multivariable model adjusted for age, sex and village, HIV (OR 83.5, 95%CI 2.01–3456, p = .020), Diabetes (OR 9.38, 95% CI 1.48–59.3, p = .017) and a farming occupation (OR 2.60, 95%CI 1.21–5.57, p = .014) were associated with MK. Compared to a low socio-economic status, a middle status was less likely to be associated with MK (OR 0.29, 95%CI 0.09–0.89, p < .0001). Conclusion : MK was associated with HIV, Diabetes, being poor and farming as the main occupation. More studies are needed to explore how these factors predispose to MK.